2020
DOI: 10.1016/j.aap.2020.105687
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019: What could be the effects on Road safety?

Abstract: In March 2020, the World Health Organization declared COVID-19 a worldwide pandemic. Countries introduced public health measures to contain and reduce its spread. These measures included closures of educational institutions, non-essential businesses, events and activities, as well as working from and staying at home requirements. These measures have led to an economic downturn of unprecedented proportions. Generally, as economic activity declines, travel decreases and drivers are exposed to a lower risk of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 33 publications
5
71
0
2
Order By: Relevance
“…It is important to highlight that ethnic minorities, older or employed adolescents and teens with lower prosocial tendencies appeared to be less likely to reduce their driving behavior. Recent researches have also found that especially young male drivers were more willing to exceed the speed limit and the frequency of such exceedances was higher during the COVID-19 pandemic ( Vingilis et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to highlight that ethnic minorities, older or employed adolescents and teens with lower prosocial tendencies appeared to be less likely to reduce their driving behavior. Recent researches have also found that especially young male drivers were more willing to exceed the speed limit and the frequency of such exceedances was higher during the COVID-19 pandemic ( Vingilis et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…e impact of COVID-19 has also been studied from the perspective of traffic safety. A number of negative trends in driving behaviors have been estimated, including more frequent speeding and stunt driving due to the larger amount of free time some people might generally experience [33]. Interestingly, studies that emerge within this domain have started bringing initial evidence that the COVID-19 pandemic may also promote driving more in certain groups of citizens not only due to leisure activities.…”
Section: Citizen Mobility Travel and Driving Behaviormentioning
confidence: 99%
“…Vos (2020) speculated that during mandated societal lockdown, people might be more inclined to perform activities at home which would result in less car traffic and less congestion during peak hours. Vingilis et al (2020) postulated that the adverse economic consequences of COVID-19 may improve road safety by reductions in vehicle kilometers travelled, number of higher risk drivers on roads; and travel for entertainment and leisure activities. Stavrinos et al (2020) found a 37 % reduction in driving days per week and 35 % reduction in vehicle miles driven among adolescents during COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was no change in volume of heavy vehicle traffic and the volume may have increased to meet the supply needs ( What are the impacts of the COVID-19 pandemic on our transport systems, 2020 ). Speeding and stunt driving may also have increased during COVID-19 pandemic ( Vingilis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%